PANCASILA, DEMOCRACY, AND NKRI BER-SHARĪ’AH IN INDONESIA: HOW CHRISTIANS SHOULD RESPOND AND PARTICIPATE - Andreas Jonathan (Prodi Studi Agama-agama Fakultas Ushuluddin dan Dakwah IAIN Kediri, 2019)
Democracy, pluralism, Pancasila, and religious freedom become a heated debate in Indonesia because they arenot only theoretical and conceptual but also have a significant influence on many aspects of the nation’s life.Moreover, the demand for the implementation of sharī’ah from a small number of Muslim groups continues toechoe in this country which, off course, concern also the Christians who become the second largest populationin this country. This paper is an attempt to examine the Christians’ participation in democracy and Pancasilaamids the demand for the implementation of sharī’ah in Indonesia. It discusses theological perspectives forChristians’ participation in the public space, a brief history of the struggle on sharī’ah law and Pancasila, andhow Christians have and should respond through civil society. The paper argues that Christians can participatein many ways in democratization and defending Pancasila in Indonesia through the channels of civil society.